2005
DOI: 10.1039/b414747m
|View full text |Cite
|
Sign up to set email alerts
|

The synthesis and conformation of oxygenated trianglimine macrocycles

Abstract: The synthesis of series of D(2h) and C(2v) symmetric oxygenated aromatic dicarboxaldehydes, using dilithiation methodology, is described along with their reactivity in the [3+3] cyclocondensation reaction with (1R,2R)-diaminocyclohexane to give oxygenated trianglimine macrocycles. Macrocycles derived from C(2v) symmetric dialdehydes give macrocycles with a stereogenic aromatic plane with complete diastereocontrol, as a mixture of rotamers.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
63
0

Year Published

2006
2006
2018
2018

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 66 publications
(67 citation statements)
references
References 39 publications
4
63
0
Order By: Relevance
“…1 H NMR (500 MHz, CDCl 3 ) δ/ppm 10.52 (s, 2H, H CHO ), 7.43 (s, 2H, H C3 ), 4.05 (t, J = 6.5 Hz, 4H, H a ), 1.93–1.74 (m, 4H, H b ), 1.06 (m, J = 7.4 Hz, 6H, H c ). This matches the literature data [26]. …”
Section: Methodssupporting
confidence: 92%
See 1 more Smart Citation
“…1 H NMR (500 MHz, CDCl 3 ) δ/ppm 10.52 (s, 2H, H CHO ), 7.43 (s, 2H, H C3 ), 4.05 (t, J = 6.5 Hz, 4H, H a ), 1.93–1.74 (m, 4H, H b ), 1.06 (m, J = 7.4 Hz, 6H, H c ). This matches the literature data [26]. …”
Section: Methodssupporting
confidence: 92%
“…Compound 8a (Scheme 3) was prepared from the commercially available 2,5-dibromohydroquinone and then reacted with n BuLi followed by DMF to yield the dialdehyde 8b . The 1 H NMR spectrum of 8b was consistent with previously reported data [26]. The one-pot method of Hanan [9] (Scheme 3) was then used to transform 8b into compound 8 .…”
Section: Resultssupporting
confidence: 82%
“…Attempts to purify the compound led to decomposition. Benzyloxycarbonylphenyl)-1,3,5,7,8-pentamethyl-BODIPY (11): 2-IodoBODIPY 8 [24] (141 mg, 0.41 mmol), stannylbenzoic acid benzylester 10 [25] (250 mg, 0.50 mmol), and Pd(PPh 3 ) 4 (10 mg, 8 μmol) in dry toluene were heated to 100°C for 24 h. After removal of the solvent the mixture was subjected to silica chromatography with dichloromethane/pentane 1:1 to yield the title compound (140 mg, 0.30 mmol, 72 %). , 1 H, β-H Benzyloxycarbonylphenyl)-1,3,5,7-tetramethyl-8-mesityl-BODIPY (12): 2-IodoBODIPY 9 [ 2 6 ] (200 mg, 0.41 mmol), 4-stannylbenzoic acid benzylester 10 [25] (250 mg, 0.50 mmol) and Pd(PPh 3 ) 4 (10 mg, 8 μmol) in dry toluene were heated to 100°C for 24 h. After removal of the solvent the mixture was subjected to silica chromatography with dichloromethane/pentane 1:1 to yield the title compound (216 mg, 0.38 mmol, 93 %).…”
Section: -(4-(25-bisbenzyloxy)benzoicmentioning
confidence: 99%
“…Benzyloxycarbonylphenyl)-1,3,5,7,8-pentamethyl-BODIPY (11): 2-IodoBODIPY 8 [24] (141 mg, 0.41 mmol), stannylbenzoic acid benzylester 10 [25] (250 mg, 0.50 mmol), and Pd(PPh 3 ) 4 (10 mg, 8 μmol) in dry toluene were heated to 100°C for 24 h. After removal of the solvent the mixture was subjected to silica chromatography with dichloromethane/pentane 1:1 to yield the title compound (140 mg, 0.30 mmol, 72 %). , 1 H, β-H Benzyloxycarbonylphenyl)-1,3,5,7-tetramethyl-8-mesityl-BODIPY (12): 2-IodoBODIPY 9 [ 2 6 ] (200 mg, 0.41 mmol), 4-stannylbenzoic acid benzylester 10 [25] (250 mg, 0.50 mmol) and Pd(PPh 3 ) 4 (10 mg, 8 μmol) in dry toluene were heated to 100°C for 24 h. After removal of the solvent the mixture was subjected to silica chromatography with dichloromethane/pentane 1:1 to yield the title compound (216 mg, 0.38 mmol, 93 %). [26] (168 mg, 0.34 mmol), 4-ethinylbenzoic acid 16 [27] (50 mg, 0.34 mmol), Pd(PPh 3 ) 4 (15 mg, 13 μmol), and copper(I)iodide (10 mg, 52 μmol) in dry THF (8 mL) and Hünig base (2 mL) were stirred at 55°C for 24 h. After cooling the solvent was removed in vacuo and the residue was subjected to silica chromatography with ethyl ether/n-hexane 2:1 + 1 % acetic acid.…”
Section: -(4-(25-bisbenzyloxy)benzoicmentioning
confidence: 99%
“…Trianglamines are readily synthesized in quantitative yields by reducing trianglimines with sodium borohydride . We have shown that trianglimines can be obtained from almost any synthetically accessible aromatic dialdehyde with complete control of the size of the macrocycle and functionalities incorporated into the aromatic moiety . More importantly, we have demonstrated that trianglimines can be incorporated into more sophisticated structures such as catenanes and shown their promise in chiral recognition .…”
mentioning
confidence: 99%